Salafi Ideology and the Question of Women Empowerment among Kenyan Muslims - Mwatamu, Fatuma Kassim; Akaranga, Stephen Ifedha; Abubakar, Hashim Abdulkadir (Jurnal Kawistara, 2025)
Muslim groups that promote strict religious norms like Salafis are often associated with male dominant culture. Such a patriarchal maybe put on a question in the context in the recent global trend that significantly altered the circumstances for Muslim women, leading to a gradual shift from dependence on husbands for financial sustenance. This article investigates the primary research question: In what ways has Salafi ideology impacted the social integration and empowerment of Muslim women in Kenya? To explore this, a purposive sampling approach was employed, selecting twenty former students from the Maahad Girls’ Training Institute for a focus group discussion regarding the influence of Salafi beliefs on their lives. The study utilized Islamic critical pedagogy theory to assess how Salafi ideologies have affected the educational accomplishments of Maahad graduates, which they have utilized for self-empowerment. Furthermore, pragmatism-agency theory was instrumental in examining the social integration and empowerment of Muslim women, as well as evaluating the compatibility of Salafi beliefs with the societal context in Kenya. The findings indicate that while Salafism is frequently perceived as limiting women’s public engagement and visibility, it has been locally adapted to foster women’s empowerment. The experiences of Salafi women reveal the obstacles they encounter in achieving social integration within Kenyan society. However, they demonstrate remarkable resilience, employing various strategies to enhance their economic situations and navigate their social environments. This paper underscores the opportunities presented by the Kenyan Constitution of 2010, which champions gender equality and women’s rights, and calls for collaboration between Muslim organizations and religious institutions to educate women about available governmental resources and incentives. Such partnerships could significantly empower Muslim women and aid their integration into Kenya’s socio-economic framework.